POWER, EGO, AND POLITICAL EMBEDDEDNESS: EXPLAINING TAX AVOIDANCE IN INDONESIAN MINING COMPANIES - Supriatiningsih Supriatiningsih; Nova Rini; Pandaya Pandaya; Hidayat Darwis; Luckman Ibrahim (International Journal of Economics, Business Management and Accounting (IJEBMA), 2026)
This study examines the effect of opportunity and ego on tax avoidance and investigates the moderating role of collusion in mining companies in Indonesia within the framework of agency theory. The research population consists of 46 mining firms listed on the Indonesia Stock Exchange, using secondary data from annual reports accessed via the official exchange website (www.idx.co.id). Panel data regression is employed as the analytical technique, with data processed using Stata 17. The findings reveal that opportunity and ego do not exert a direct and significant influence on tax avoidance, suggesting that existing regulations, monitoring mechanisms, and corporate governance practices are effective in constraining opportunistic managerial behavior. However, collusion functions as a significant moderating variable: it weakens the relationship between opportunity and tax avoidance while simultaneously strengthening the effect of ego on tax avoidance. These results indicate that tax avoidance practices are more likely to emerge when individual psychological factors, particularly managerial ego, are reinforced by unethical collaborative arrangements that undermine the effectiveness of monitoring mechanisms between agents and principals.